![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
2013-06-26
展开全部
1992×19941994-1994×19931993
=1992×1001×1994-1994×1001×1993
=1001×1994×(1992-1993)【提取公因式】
=19941994×(-1)
=-19941994
=1992×1001×1994-1994×1001×1993
=1001×1994×(1992-1993)【提取公因式】
=19941994×(-1)
=-19941994
2013-06-26
展开全部
(1994-2)×19941994-1994×19931993
=1994×19941994-1994×19931993-2×19941994
=1994×(19941994-19931993)-2×19941994
=1994×1001-2×19941994
=19951994-39883988
=19931994
=1994×19941994-1994×19931993-2×19941994
=1994×(19941994-19931993)-2×19941994
=1994×1001-2×19941994
=19951994-39883988
=19931994
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询